Urban runoff impacts on particulate metal concentrations in river Seine - Estebe, A.; Mouchel, J.M.; Thevenot, D.R. (Water Air and Soil Pollution, 1998)
Metallic contents (Cd, Cu, Pb, Zn) of suspended solids (SS) were measured in two sites (Suresnes and Chatou) in the river Seine, downstream Paris, during three summer periods. These two sites, which are respectively located downstream and upstream two of the most important combined sewer overflows (CSO’s) of the Parisian sewer system (Clichy and La Briche), allow us to assess these CSO immediate impacts. Samples were collected using sediment traps, weekly during dry weather and daily during the week following the major CSO’s events. The heavy metal concentrations, relatively large but stable during summer periods, were shown to further increase downstream Paris after main rain discharges occurred. Metal concentrations measured within the Seine SS during rain events, allowed us to establish that the observable immediate impact of Clichy overflows is only 5% of what it could be. The general principle demonstrated through this work is that most SS originating from CSO’s rapidly settle once they reach the river. These polluted particles greatly contribute to the SS chronic pollution downstream Paris during dry weather, through a slow resuspension mechanism of the deposited sediments.